Effect of screw thread type on implant-related complications following femoral neck fracture fixation in non-geriatric adults: a multicenter, retrospective cohort study - Bian, Yuquan; Yang, Kai; Lin, Sen; He, Shizan; Jiang, Dajun; Jia, Weitao (Frontiers in Surgery, 2026)
IntroductionThis study compared implant-related complications after femoral neck fracture fixation using partially vs. fully threaded cannulated screws in non-geriatric patients.MethodsThis retrospective cohort study included 1,035 patients with femoral neck fractures aged 18–60 years treated with cannulated screws from 2012 to 2022. Patients were followed until clinical failure—defined as the occurrence of any of the following: implant cut-out, femoral neck shortening, nonunion, or avascular necrosis—or for a minimum of 2 years. Patients were categorized into two groups according to thread type and balanced using propensity score matching. The primary outcome was the clinical failure rate. Subgroup analyses were performed for comminuted vs. non-comminuted fractures.ResultsThe overall clinical failure rate was 35.4%, including implant cut-out (1.9%), femoral neck shortening (15.0%), nonunion (9.3%) and avascular necrosis (23.5%); this rate was significantly higher for those with comminuted fractures. After balancing covariates, the partially threaded group demonstrated higher rates of femoral neck shortening (13.7% vs. 6%, p = 0.017) and avascular necrosis (17.9% vs. 9.5%, p = 0.027) than the fully threaded group in the overall cohort. In the non-comminuted subgroup, the partially threaded group was associated with significantly lower rates of implant cut-out (0% vs. 8.7%, p < 0.01) than the fully threaded group. However, in the comminuted fracture subgroup, the fully threaded group exhibited significantly lower incidences of femoral neck shortening (6.6% vs. 22.4%, p < 0.01) and avascular necrosis (10.5% vs. 36.2%, p < 0.01).ConclusionsFracture comminution increases the risk of femoral neck shortening and avascular necrosis. In non-comminuted fractures, the use of partially threaded screws should be prioritized. However, in comminuted fractures, using fully threaded screws decreases rates of femoral neck shortening and avascular necrosis. This study provides evidence to guide cannulated screw thread type selection for comminuted fractures and paves the way for future randomized controlled trials.